The Analysis of Factors Related to Self Care of Men Who Have Sex with Men (MSM) with HIV/AIDS - Inriyana, Ria; Wisaksana, Rudi; Ibrahim, Kusman (Universitas Pendidikan Indonesia, 2021)
ABSTRACTIntroduction :Â Men who have sex with men (MSM) contain the highest risk factor and contribute significantly to HIV / AIDS transmission. As a chronic disease, MSM with HIV / AIDS needs treatment and care for the rest of their lives. The complexity of HIV disease and its treatment makes self-care essential for the optimal health of people living with HIV. The Health Belief Model (HBM) factors can explain and predict self-care behavior in MSM with HIV/AIDS. Objectives :This study aims to analyze the dominant factors associated with self-care of MSM with HIV / AIDS. Methods: This research uses quantitative methods with correlation analytic design. The sampling process employed a purposive sampling of 78 respondents. Primary data collection was processed by a self-care assessment questionnaire and HBM through google forms online survey. The data were analyzed using the Pearson product-moment correlation test and multiple linear regression.Â Results: The results showed that the highest mean HBM was in perceived self-efficacy (23.18) and self-care in the spiritual domain (24.94). The bivariate results showed that self-care had a significant relationship with perceived susceptibility (r = 0.346, p 0.05), perceived benefits, (r = 0.255, p 0.05), and perceived self-efficacy (r = 0.406, p 0.05). The multivariate results found that perceived self-efficacy is the dominant factor (Î² = 0.406) which is related to the respondentâ€™s self-care ability. Discussion: Most respondents have the belief that they are capable of self-care the higher the perceived self-efficacy, the better the chance of having self-care. Services that respect and value MSM as humans by providing motivation through counseling during Voluntary Counseling and Testing (VCT) play a role in maintaining and increasing perceived self-efficacy. Nursing care that is carried out with the belief that everyone has the ability to care for themselves can help the individual meet the needs of life, maintain health and well-being.ABSTRAKPendahuluan : Lelaki Seks Lelaki (LSL) merupakan faktor risiko tertinggi dan memberikan kontribusi penularan HIV/AIDS yang signifikan. Sebagai penyakit kronis, LSL dengan HIV/AIDS perlu melakukan pengobatan dan perawatan seumur hidupnya.Kompleksitas penyakit HIV dan pengobatannya membuat perawatan mandiri (self-care) penting untuk kesehatan ODHA yang optimal. Melalui faktor-faktor Health Belief Model (HBM) dapat menjelaskan dan memprediksi perilaku self-care pada LSL dengan HIV/AIDS. Tujuan : Penelitian ini bertujuan untuk menganalisis faktor dominan yang berhubungan dengan self-care LSL dengan HIV/AIDS. Metode : Penelitian ini menggunakan metode kuantitatif dengan desain analitik korelasi. Penarikan sampel menggunakan purposive sampling sebanyak 78 responden. Pengumpulan data primer dengan kuesioner self-care assessment dan HBM melalui online survey menggunakan google formulir. Data di analisis menggunakan uji korelasi pearson product moment dan regresi linier ganda. Hasil : Hasil penelitian didapatkan rerata HBM tertinggi pada perceived self efficacy (23.18) dan self-care pada domain spiritual (24.94). Hasil bivariat menunjukkan bahwa self-care memiliki hubungan yang signifikan dengan perceived susceptibility (r=0.346,p0.05), perceived benefits, (r=0.255,p0.05),dan perceived self-efficacy (r=0.406,p0.05). Hasil multivariat ditemukan bahwa perceived self efficacy merupakan faktor dominan (Î²=0.406) yang berhubungan dengan kemampuan self-care responden. Diskusi : Sebagian besar responden memiliki keyakinan bahwa dirinya mampu untuk melakukan perawatan mandiri, semakin tinggi perceived self efficacy maka berpeluang memiliki self-care yang semakin baik. Layanan kesehatan yang menghormati dan menghargai LSL sebagai manusia dengan pemberian motivasi melalui konseling saat Voluntary Counseling and Testing (VCT) berperan guna mempertahankan dan meningkatkan perceived self efficacy. Asuhan keperawatan yang dilakukan dengan keyakinan bahwa setiap orang mempunyai kemampuan untuk merawat diri sendiri dapat membantu individu tersebut memenuhi kebutuhan hidup, memelihara kesehatan dan kesejahteraan.